2021
DOI: 10.1007/s10989-021-10284-y
|View full text |Cite
|
Sign up to set email alerts
|

Viral 3CLpro as a Target for Antiviral Intervention Using Milk-Derived Bioactive Peptides

Abstract: Viruses of the picornavirus-like supercluster mainly achieve cleavage of polyproteins into mature proteins through viral 3-chymotrypsin proteases (3C pro ) or 3-chymotrypsin-like proteases (3CL pro ). Due to the essential role in processing viral polyproteins, 3C pro /3CL pro is a drug target for treating viral infections. The 3CL pro is considered the main protease (M pro ) of coronaviruses. In the current study, the SARS-CoV-2 M pro inhibitory activity of di-and tri-peptides (DTPs) resulted from the proteoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The effect of dairy on COVID-19 is greatly focused on fermented dairy products, mainly on those including probiotics, which is not consistent with our results, and are associated with an enhanced immunity and lower risk of infectious diseases, including COVID-19 (mainly based on the modulation of intestinal microbiome) ( 15 , 16 , 30 , 35 , 47 , 48 ). Similarly, there is evidence on the immune modulatory role of raw cow's milk on respiratory infections ( 49 ), and even a recent publication has also shown activity against SARS-CoV-2 of some milk-derived bioactive peptides ( 47 , 50 ). However, there are also publications that describe mechanisms that could explain the association found in this work.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of dairy on COVID-19 is greatly focused on fermented dairy products, mainly on those including probiotics, which is not consistent with our results, and are associated with an enhanced immunity and lower risk of infectious diseases, including COVID-19 (mainly based on the modulation of intestinal microbiome) ( 15 , 16 , 30 , 35 , 47 , 48 ). Similarly, there is evidence on the immune modulatory role of raw cow's milk on respiratory infections ( 49 ), and even a recent publication has also shown activity against SARS-CoV-2 of some milk-derived bioactive peptides ( 47 , 50 ). However, there are also publications that describe mechanisms that could explain the association found in this work.…”
Section: Discussionmentioning
confidence: 99%
“… 985 Behzadipour et al evaluated the SARS-CoV-2 Mpro inhibitory activity of 326 di- and tripeptides from the proteolysis of bovine milk proteins by docking. 986 Some works 974 , 987 , 988 aimed to repurpose peptides from seed proteins to targets Mpro, S protein, and PLpro. Some molecular modeling studies of the protein–protein binding were also contributed to treating SARS-CoV-2.…”
Section: Methods and Approachesmentioning
confidence: 99%
“…Zhao et al.’s docking studies identified GSRY among lactoferrin-derived peptides is potent to Mpro . Behzadipour et al evaluated the SARS-CoV-2 Mpro inhibitory activity of 326 di- and tripeptides from the proteolysis of bovine milk proteins by docking . Some works ,, aimed to repurpose peptides from seed proteins to targets Mpro, S protein, and PLpro.…”
Section: Methods and Approachesmentioning
confidence: 99%
“…servations are yet to be confirmed in in vitro and in vivo studies. Behzadipour et al (2021) also documented the antiviral role of milk peptides obtained by the proteolysis of bovine milk CNs and WPs.…”
Section: S No Type Of Whey Proteins Name Of Virus In Vitro Mechanism ...mentioning
confidence: 97%